CHRONIC KIDNEY DISEASE AND VISCERAL CANDIDIASIS - V. Moyseyenko; T. Nykula; I. Burzhynskaya (Ukrainian Journal of Nephrology and Dialysis, 2015)
Kidneys play a significant role in metabolism, detoxification, biotransformation of dietary, medicinal and other substances. The mainstay of treatment of patients with chronic kidney disease, including pyelonephritis is antibiotic therapy; of glomerulonephritis - glucocorticoids, cytostatics. The presence of comorbidities, diabetes increases the total number of drugs used. Frequent prolonged use of drugs causes secondary immunodeficiency, gastrointestinal tract dysbiosis, clinical manifestations of which are oral mucosa candidiasis; the progression of kidney damage, kidney transplant may cause visceral candidiasis. Control of immunosuppressive therapy, parenteral infusion ofantifungal agents and timely diagnosis prevent candidiasis in patients with chronic kidney disease.